A whey-supplemented, high-protein diet versus a high-carbohydrate diet: Effects on endurance cycling performance - Macdermid, P. W.; Stannard, S. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study compared a training diet recommended for endurance athletes (H-CHO) with an isoenergetic high protein (whey supplemented), moderate carbohydrate (H-Pro) diet on endurance cycling performance. Over two separate 7-d periods subjects (n= 7) ingested either H-CHO (7.9 ± 1.9 g · kg-1 · d ± 0.3 g · kg-1 · d-1 fat; 1.3 ± 0.4 g · kg-1 · d-1 protein) or H-Pro (4.9 ± 1.8 g · kg-1 · d-1;1.3 ± 0.3 g · kg-1 · d-1; 3.3 ± 0.4 g · kg-1 · d-1) diet in a randomized, balanced order. On day 8 subjects cycled (self-paced) for a body weight dependent (60 kJ/bm) amount of work. No differences occurred between energy intake (P = 0.422) or fat intake(P = 0.390) during the two dietary conditions. Performance was significantly (P = 0.010) impaired following H-Pro (153 ± 36) compared with H-CHO (127 ± 34 min). No differences between treatments were observed for physiological measures taken during the performance trials. These results indicate an ergolytic effect of a 7-d high protein diet on self-paced endurance cycling performance.